Understanding Changes in Poverty - Inchauste, Gabriela (World Bank, 2015)
The 2015 Millennium Development Goal to cut in half the share of the world?s population living in extreme poverty was met with time to spare. By 2013, the percentage of developing-country populations living in extreme poverty decreased from 43 percent in 1990 to 21 percent by 2010. Clearly, there is still a long way to go, with 1.2 billion people without enough to eat. What can we learn from the recent success?